2006
DOI: 10.1080/19485565.2006.9989115
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related patterns of urinary Gonadotropins (FSH and LH) and E‐3‐G as measures of reproductive function among Turkana Males of Northern Kenya

Abstract: To determine age-related patterns of gonadotropins and their relationship to energetic status in a subsistence population we analyzed urinary FSH, LH, and estrone-3-glucuronide (E-3-G) along with anthropometric measures among Turkana males of northern Kenya. Subjects were 134 nomadic and 109 settled males ages 20 to 80+. FSH, LH and E-3-G were significantly higher among the settled, compared to nomadic, males. LH, but not FSH, showed a significant increase across 10 year age groups among all the men. E-3-G inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…40 In contrast, urinary FSH and LH levels among Turkana men of Kenya showed increases in well-fed sedentary men but not undernourished nomads. 41 Moreover, average LH and FSH levels were significantly higher among well-fed settled versus undernourished nomadic Turkana men. However, caution is warranted when interpreting urinary gonadotropin levels in response to undernutrition because urinary levels of LH and FSH increase significantly without concurrent changes in serum levels in response to fasting in men, suggesting altered renal clearance that is independent of pituitary production.…”
Section: Sex Hormone Variationmentioning
confidence: 90%
See 1 more Smart Citation
“…40 In contrast, urinary FSH and LH levels among Turkana men of Kenya showed increases in well-fed sedentary men but not undernourished nomads. 41 Moreover, average LH and FSH levels were significantly higher among well-fed settled versus undernourished nomadic Turkana men. However, caution is warranted when interpreting urinary gonadotropin levels in response to undernutrition because urinary levels of LH and FSH increase significantly without concurrent changes in serum levels in response to fasting in men, suggesting altered renal clearance that is independent of pituitary production.…”
Section: Sex Hormone Variationmentioning
confidence: 90%
“…E-3-G levels were positively associated with age in the settled well-fed population. 41 Follicle stimulating hormone (FSH) and LH are gonadotropins produced by the pituitary under control of gonadotropin-releasing hormone (GnRH) from the hypothalamus. FSH is involved with spermatogenesis whereas LH stimulates testosterone production.…”
Section: Sex Hormone Variationmentioning
confidence: 99%
“…However, work from small‐scale and non‐Western societies have found that some age‐related physiological processes, including cardiovascular function and hormone levels, thought to be inevitable, may in fact not be (Ellison et al, ; Gurven, Blackwell, Eid Rodríguez, Stieglitz, & Kaplan, ; Kaplan et al, ; Kurita et al, ; Mueller, Noya‐Alarcon, Contreras, Appel, & Dominguez‐Bello, ; Raichlen et al, ; Uchida et al, ). When lifestyle, nutrition, energetic status, and population variation of biomarker levels have been explored, the biological inevitability of senescence as exhibited in Western populations comes into question (Campbell, Leslie, & Campbell, , ; Ellison et al, ; Uchida et al, ).…”
Section: Introductionmentioning
confidence: 99%